Identidades monstruosas como síntoma de la crisis moral en la sociedad actual: Ejemplo de tres autores hispanoamericanos - Matić, Gordana (Verbum – Analecta Neolatina, 2021)
The present article has a dual theoretical frame. It uses Donna Haraway’s “A Cyborg Manifesto” as well as Jeffrey Jerome Cohen’s Monster Theory in order to observe how three contemporary Latin American authors approach the processes of the identity formation while deconstructing hegemonic discourses dominant in Occidental post-industrial societies. The subjects of our analysis are products of anti-natural crossbreeding between humans and birds in the novel Diario de la gentepájaro (2008) of Venezuelan writer Wilfredo Machado, the hybrid beasts presented in Bestiario de seres prodigiosos (2001) of the Mexican author René Avilés Fabila and finally techno-human protagonists created by Cuban short story writer Jorge Enrique Lage. For these writers, any kind of human hybridization – cultural, racial, ethnic, or national – is not convincing enough to show the moral crisis the humanity is going through, therefore they reach out for monstrosity that seems to be appropriate symptom of ecological, technological, social, or cultural aspects of that crisis.